Complications of COVID-19 in patients with systemic arterial hypertension: an integrative review (Research, Society and Development, 2022)
The present work consists of an integrative literature review with the objective of identifying in the main available journals (PUBMED, LILACS, VHL) the current evidence on the consequences arising from the combination of both diseases, evaluating the possible aggravations in the cases of patients in which there was an association between COVID-19 and SAH compared to patients with COVID-19 exclusively. The results were synthesized and later critically analyzed based on their division into 5 parameters that involved the relationship of SAH with the severity of COVID-19, the increase in unfavorable outcomes, the development of complications related to SARS-CoV-2 infection, the alteration of biomarkers and finally the relationship between SAH and mortality in patients infected with SARS-CoV-2. It is concluded that patients with SAH are more likely to develop a negative prognosis in the face of COVID-19, especially considering the admission of patients to an intensive care unit (ICU), need for invasive ventilation, mortality and morbidity in general, being, therefore a risk factor of great relevance with regard to infection by SARS-CoV-2.